Зіставлення континууму семантичних позицій вербальної зони типових словотвірних парадигм дієслів-ономатопів на позначення звуковияву в процесі споживання в українській і польській мовах - Kushlyk, Oksana (Theoria et Historia Scientiarum, 2025)
The article compares the derivational capacity of onomatopoeic verbs with the semantics of vocal imitation of the sound to form verbatives in the process of consumption in the Ukrainian and Polish languages. The author emphasizes the necessity of such a study, which is related to further development of the stem-centric derivatology in each of the languages, with one of its areas being comparative studies of word formation in order to delineate the typological role of the stem in various derivational processes. The article highlights the determination of the word-forming capacities of verbs as base words by their primarily general features, including semantic, morphological and syntactic, as well as by their partial features inherent only to this lexical-grammatical word category, among other things, by predisposition of their semantics to polysemy, the specifics of categorizing extra-linguistic reality, etc. The research is based on the word-formation paradigmatic mechanism of analyzing factual material with a focus on verbal deverbatives, which formed the verbal zone of typical word-formation paradigms as indicators of the word-formation capacity of words in each of the languages. The author inventories all derivatives within this zone, establishes the continuum of realized semantic positions, identifies the arsenal of word-forming means used to create derivatives, traces their ability to develop additional semantic shades, etc. It is concluded that the word-forming capacity of onomatopoeic verbs with the semantics of vocal imitation of the sound is relatively similar in terms of the ability to realize the established semantic positions in the process of consumption: the relativity is determined, on the one hand, by the kinship of the Ukrainian and Polish languages, and on the other hand, by the peculiarities of the grammatical system of each language.